Identification and analysis of Garbage code occurred when filling out the Death Certificate at the Hospital Geral de Nova Iguaçu - RJ, a reality to be modified (Research, Society and Development, 2020)
The death certificate is of paramount importance in the field of public health, being used as a tool to trace epidemiological indicators for future preventive health policies. Objective: to identify the main errors and / or inconsistency of information, Garbage Code (CG), belonging to the ICD-10 when filling in the death certificates of Hospital Geral de Nova Iguaçu. Method: this is an exploratory scientific work, which is based on the search for information through the Mortality Information System (SIM) of the Informatics Department of the Unified Health System (DATASUS), bibliographic review and field research. Result: the number of CG cases produced in Nova Iguaçu was 3058 cases, among them, 1963 were produced at the Hospital Geral de Nova Iguaçu. Conclusion: This study points out the importance of implementing measures, such as continuing education lectures and valuing the importance of the death certificate, in order to minimize the amount of GC and provide greater reliability to the SIM, which is an important tool for epidemiological statistics and planning of public preventive health policies.